Influenza in feral cat populations: insights from a study in North-East Italy - Cavicchio, Lara; Campalto, Mery; Carrino, Marilena; Lucchese, Laura; Ceglie, Letizia; Fincato, Alice; Boscolo Cegion, Lorenza; Mazzotta, Elisa; Beato, Maria Serena; Natale, Alda (Frontiers in Veterinary Science, 2024)
Influenza A virus (IAV) can cause high morbidity and mortality in domestic and wild avian species and it is able to infect mammals as well. IAV in cats is sporadic and self-limiting but the recent findings of high pathogenicity avian influenza virus (HPAIV) with genetic signatures of mammalian adaptation, in domestic cats, has raised new concerns about the potential role of cats in the virus ecology. The present study aimed to investigate the circulation of IAV in companion animals' shelters in Northeastern Italy. All samples were collected from feral cats living in feline colonies that were hosted in the companion animals' shelters for the requisite period to administer the veterinary treatments. Between 2021 and 2022, 389 oropharyngeal swabs and 279 sera were collected. All swabs tested negative for IAV and the only one ELISA positive serum sample resulted H5 positive by HI test with a titre of 1:80. Despite the sporadic occurrence of influenza in cats, continuous monitoring is crucial due to the evolving zoonotic nature of the virus.